Education and Poverty: A Panel Data Approach for a Sample of Developing Countries - CHEMLI, Leila (Journal of Posthumanism, 2025)
This study examines the relationship between access to education and poverty alleviation in 40 developing countries from 2000 - 2022. Using fixed and dynamic effects in an econometric panel data model, the study finds that coverage of primary schooling, coverage of secondary schooling, and the share of educated adults significantly reduces the incidence of monetary poverty. The effect is moderated by income inequality and level of economic development. The implications call for an in combination approach to educational access with redistributive policies and the quality of teachers. Overall, this study provides a grounded set of policy recommendations to improve how educational access relates to poverty alleviation.